2008
DOI: 10.1002/j.2161-1882.2008.tb00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Care in College Health: A Case Study

Abstract: This case study describes 1 international student's treatment experience with an integrated health program on a college campus. This program uses a multidisciplinary, mind-body approach, which incorporates individual counseling, primary care, psychiatric consultation, a mindfulness-based cognitive therapy class, and a meditation group. T oday's college counseling centers are being used by students who have mental health concerns that are increasingly severe and accompanied by symptoms that threaten academic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Moreover, because many mental health issues cause physical symptoms, many students seek evaluation at health clinics first (ACHA, 2010b). The few studies examining IBHC within university health settings have reported numerous benefits, including increased accessibility of mental/behavioral health care, increased referral follow-through, and higher quality patient care (Masters, Stillman, Browning & Davis, 2005; Tucker, Sloan, Vance, & Brownson, 2008; Westheimer & Steinley-Bumgarner, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, because many mental health issues cause physical symptoms, many students seek evaluation at health clinics first (ACHA, 2010b). The few studies examining IBHC within university health settings have reported numerous benefits, including increased accessibility of mental/behavioral health care, increased referral follow-through, and higher quality patient care (Masters, Stillman, Browning & Davis, 2005; Tucker, Sloan, Vance, & Brownson, 2008; Westheimer & Steinley-Bumgarner, 2008).…”
mentioning
confidence: 99%
“…Preliminary studies have begun to examine patient and provider opinions about IBHC within the college health setting. Tucker et al (2008) examined an international student's experience of the Integrated Health Program at the University of Texas at Austin using a case study design and found his overall experience to be positive. Westheimer and Steinley-Bumgarner (2008) examined provider behaviors, opinions, and experiences during the integration process of IBHC within the same university and found PCPs ascribed a high level of value to the collaborative effort integrated BHPs could provide in helping with a diverse number of conditions.…”
mentioning
confidence: 99%
“…Prior journal articles have discussed implementing this type of integrated model within university health centers; however, they have focused on describing the process of creating a training program for clinical psychology doctoral students (e.g., Masters, Stillman, Browning, & Davis, 2005) or have explored patient (Tucker, Sloan, Vance, & Brownson, 2008) or provider (Alschuler, Hoodin, & Byrd, 2008; Cowan & Morewitz, 1995; Westheimer, Steinley-Bumgarner, & Brownson, 2008) perceptions of the integrated care model in a college health care setting. In fact, our initial work (Funderburk, Fielder, DeMartini, & Flynn, 2012) describes how both patients and providers found the integrated health care achieved through the use of practicum students at a university clinic to improve clinical care.…”
mentioning
confidence: 99%
“…Student health and wellness initiatives also stand to gain from collaboration across disciplines. For example, Tucker, Sloan, Vance, and Brownson (2008) illustrated the positive collaboration between the college counseling center, health center, and an academic class to aid in the adjustment of an international student. Likewise, Ott, Haertlein, and Craig (2003) described an initiative to reduce high-risk drinking involving a partnership between faculty and student affairs on a university campus.…”
mentioning
confidence: 99%